Healthcare providers' attitudes towards delay in cancer treatment during COVID-19 pandemic. Issue 2 (March 2023) - Kaur, Anahat; Pergolotti, Mackenzi; Battisti, Nicolo; Krok-Schoen, Jessica L.; Cabrera Chien, Leana; Canin, Beverly; Malone, Mariuxi Viteri; MacKenzie, Amy; Ali, Imran; Streck, Brennan; Shahrokni, Armin; Plotkin, Elana; et al.
Abstract: Introduction: The COVID-19 pandemic has created unprecedented obstacles leading to delays in treatment for older adults with cancer. Due to limited resources at the height of the pandemic, healthcare providers were constantly faced with ethical dilemmas regarding postponing or rescheduling care for their patients. Materials and Methods: Two survey-based studies were conducted at different time-points during the pandemic looking at factors affecting oncology care providers' attitudes towards delay in treatment for older adults with cancer. Eligible participants were recruited by email sent through professional organizations' listservs, email blasts, and social media. Change in provider attitude over time was analyzed by comparing responses from the 2020 and 2021 surveys. Data analysis included descriptive statistics and chi-squares. Results: In 2020, 17.5% of respondents were strongly considering/considering postponing cancer treatment for younger patients (age 30 and below), while 46.2% were considering delaying treatment for patients aged >85. These responses were in stark contrast to the results of the 2021 survey, where only 1.4% of respondents strongly considered postponing treatment for younger patients, and 13.5% for patients aged >85. Discussion: All recommendations to postpone treatment for older adults with cancer must be made after mutual discussion with the patient. Throughout the COVID-19 pandemic, oncology care providers had to consider multiple factors while treating patients, frequently making most decisions without appropriate institutional support.